Issue Information. Issue 1 (12th March 2020) - Unknown
Abstract : Cover : In Gu et al. (http://doi.org/10.1002/cpmo.67 ) image shows schematics for designing single guide RNA and repair template. (A ) Designs for fusion insertion. (B ) Designs for IRES or 2A separated insertion. (C ) Designs for conditional alleles. (D ) Designs for gene‐swapping alleles.